2016
DOI: 10.1186/s40064-016-3260-8
|View full text |Cite
|
Sign up to set email alerts
|

Economic returns in forming stable R&D networks

Abstract: The aim of this paper is to study the individual and social benefits behind constructing stable R&D networks. We find that the equilibrium outcomes of a stable network are related to the number of competitors. As they increase, the individual outcomes and the total welfare decrease. This implies that in the individual and social perspectives, small stable networks are more desirable than the large ones. Furthermore, when comparing the stability of the components of a network with a complete network, we conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The paper also discusses the consistency of our empirical results with the theoretical results of R&D cooperation (e.g., Alghamdi [1], D'Aspremont and Jacquemin [7], Deroian [8], Goyal and Moraga-Gonzalez [12], Goyal and Joshi [13], and Westbrock [37]). Among the various models applied in R&D, the authors studied the incentives for companies to cooperate in R&D and the potential consequences for other economic factors.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…The paper also discusses the consistency of our empirical results with the theoretical results of R&D cooperation (e.g., Alghamdi [1], D'Aspremont and Jacquemin [7], Deroian [8], Goyal and Moraga-Gonzalez [12], Goyal and Joshi [13], and Westbrock [37]). Among the various models applied in R&D, the authors studied the incentives for companies to cooperate in R&D and the potential consequences for other economic factors.…”
Section: Introductionsupporting
confidence: 71%
“…As well as the importance of networks in identifying profitable structures for all companies. There are several studies that have used the network framework to study the impact of R&D cooperation on economic outcomes (e.g., Alghamdi [1], Deroian [8], and Westbrock [37]).…”
Section: Experimental Vs Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Goyal and Moraga-Gonzalez found that the low density network G 3 is stable for small values of the R&D spillover (see Figure 4 for the list of asymmetric networks with three firms). e Regarding to equation (11), see the equilibria under the symmetric networks in the Appendix.…”
Section: Endnotesmentioning
confidence: 99%